Fixed point theorems for non-self maps I - Troy L. Hicks; Linda Marie Saliga (International Journal of Mathematics and Mathematical Sciences)
Suppose f:C→X where C is a closed subset of X. Necessary and sufficient conditions are given for f to have a fixed point. All results hold when X is complete metric space. Several results hold in a much more general setting.